Anemia in young patients with ischaemic stroke. (24th February 2015) - Kellert, L.; Kloss, M.; Pezzini, A.; Metso, T. M.; Metso, A. J.; Debette, S.; Leys, D.; Caso, V.; Thijs, V.; Bersano, A.; Touzé, E.; Tatlisumak, T.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose To investigate the association of anemia on admission with ischaemic stroke (IS), stroke severity and early functional outcome in patients with cervical artery dissection (CeAD) or with IS of other causes (non‐CeAD‐IS patients). Methods The study sample comprised all patients from the Cervical Artery Dissection and Ischaemic Stroke Patients (CADISP) study without pre‐existing disability and with documentation of stroke severity and hemoglobin (Hb) concentration on admission. Anemia was classified as mild (Hb < 12 g/dl in women and Hb < 13 g/dl in men) or moderate to severe (Hb < 10 g/dl in women and Hb < 11 g/dl in men). Stroke severity on admission was assessed with the National Institutes of Health Stroke Scale (NIHSS). Outcome after 3 months was assessed with the modified Rankin Scale (mRS‐3mo). Unfavorable outcome was defined as mRS‐3mo ≥ 3. Results Amongst 1206 study patients (691 CeAD and 515 non‐CeAD), 87 (7.2%) had anemia, which was moderate to severe in 18 (1.5%) patients. Anemia was associated with female sex in both study samples, but no further associations with risk factors or comorbidities were observed. In CeAD patients, anemia was associated with occurrence of stroke (P = 0.042). In both study samples, anemic patients had more severe strokes (CeAD, P = 0.023; non‐CeAD, P = 0.005). Functional outcome was not associated with anemia in general, but moderate to severe anemia was significantly associated with unfavorable outcome (P = 0.004). Conclusion Anemia on admission was associated with stroke in CeAD patients and with more severe strokes in both study samples. Moderate to severe anemia may predict unfavorable outcome.